(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Introduzione - 2. La logica dell’uniformazione - 3. Due significati di “complessità”. The complexity of personal laws and the debate on the Uniform Civil Code in India ABSTRACT: The promulgation of the Uniform Civil Code, envisaged in the Indian Constitution as a Directive Principle of State Policy, has been at the center of a debate on overcoming the application of personal laws in matters of family and succession that has always been present in the Indian context and has recently been revived. The contribution identifies as useful keys for analysis on the one hand the logic of uniformisation as choice and, on the other hand, complexity, understood both as the operational difficulty of managing a system of laws applied on a personal basis and as a basic feature of continuous interactions between different principles and rules in a highly pluralistic context.